Exploring Digital Native News Media - Salaverría, Ramón (2020)
Digital native news media are becoming a blooming phenomenon, expanding globally. Up until now, however, the scholar community has paid little attention to online-born media, compared to the high interest devoted to the legacy media brands. Drawing upon the extant literature on this emerging topic, this editorial summarizes the empirical and theoretical contributions of the thematic issue entitled “Digital Native News Media: Trends and Challenges.” The author highlights that the studies selected for this thematic issue not only explore the innovative characteristics and opportunities of digital native media in thirty countries, but also provide a cautionary tale about their structural problems and limitations.